VD_FINDINFO Jug / 2024 / 28 vom 18. Januar 2024 - VD Tribunal cantonal (2024)
ÉCONOMIE DU TRAITEMENT, AM, LOI FÉDÉRALE SUR L'ASSURANCE-MALADIE, RESTITUTIONEN GÉNÉRAL | 32 al. 1 LAMal, 43 LAMal, 44 LAMal, 56 LAMal, 89 LAMal